Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1007/s10661-015-5001-9
|View full text |Cite
|
Sign up to set email alerts
|

The influences of selected soil properties on Pb availability and its transfer to wheat (Triticum aestivum L.) in a polluted calcareous soil

Abstract: Accumulated anthropogenic heavy metals in the surface layer of agricultural soils may be transferred through the food chain via plant uptake processes. The objectives of this study were to assess the spatial distribution of lead (Pb) in the soils and wheat plants and to determine the soil properties which may affect the Pb transferring from soil to wheat plants in Zanjan Zinc Town area, northwestern Iran. A total of 110 topsoil samples (0-20 cm) were systematically collected from an agricultural area near a la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…The same trends were observed for the different soils (FOS_R, FOS_U, FOS_I), with the largest DTPA fraction observed in soils of urban plot for all these elements. These results appeared in line with previous studies carried out on calcareous soils of the Mediterranean region (Testiati, 2012;Safari et al, 2015;Austruy et al, 2016). The FOS_I/FOS_R ratios ranged from 1.1 (Cu) to 3.9 (Al) for poplar trees and between 0.8 (Cu, Zn) and 3.5 (Sr) for pines.…”
Section: Pseudototal and Bioavailable Concentrations In Soilssupporting
confidence: 92%
See 1 more Smart Citation
“…The same trends were observed for the different soils (FOS_R, FOS_U, FOS_I), with the largest DTPA fraction observed in soils of urban plot for all these elements. These results appeared in line with previous studies carried out on calcareous soils of the Mediterranean region (Testiati, 2012;Safari et al, 2015;Austruy et al, 2016). The FOS_I/FOS_R ratios ranged from 1.1 (Cu) to 3.9 (Al) for poplar trees and between 0.8 (Cu, Zn) and 3.5 (Sr) for pines.…”
Section: Pseudototal and Bioavailable Concentrations In Soilssupporting
confidence: 92%
“…The soils of the area were slightly alkaline (pH = 7.66 ± 0.39, 7.48 ± 0.25 and 7.50 ± 0.23 respectively for rural, urban and industrial areas) responsible for a low mobility of most of the TEs, which did not exceed 5 % of the pseudototal concentration or were very low with values close to the percent or even the thousandth for As, Cr, Co, Mn, Mo, Ni, Sb and V. On the contrary, important exchangeable fractions were measured for Cd (between 21.6 and 23.5 %) and to a lesser extent for Cu, Pb and Zn, of which the DTPA-extractable fraction represented between 3 and 10 % of the pseudototal fraction. This can be explained by the strong affinity of Cu and Pb for dissolved organic matter (Komarek et al, 2008, Kelepertzis et al, 2015, Safari et al, 2015. Indeed, Wu et al (2002) found that a high pH favours the dissolution of humic acids and increases the dissolved concentration of metals due to the formation of metal-organic complexes in solution.…”
Section: Pseudototal and Bioavailable Concentrations In Soilsmentioning
confidence: 99%
“…Cu, Zn, Pb, and Cd exhibited good correlations between grains and soils, soils and roots with the exception of Zn in grains and soils. It has been known that generally these elements in wheats came mainly from soils (Wang et al, 2012b;Çıçek et al, 2013;Wahsha et al, 2014;Safari et al, 2015) although few studies reported that Pb accumulation in wheat samples was mainly contributed by atmospheric deposition, rather than the contaminated soil (Yang et al, 2015). The significant correlations for Hg were only found between soils and roots, stems and leaves, and leaves and shells.…”
Section: Principal Source Of Hg In Wheatsmentioning
confidence: 97%
“…The application of sludge on production soil due to the stability of heavy metals in the environment can contribute to their inclusion into the biological cycle (Bose and Bhattacharyya 2008 ). Consequently, the plants absorbing soil nutrients can also assimilate heavy metals, which may lead to contamination of crops at concentrations exceeding permitted levels, which disqualifies them in terms of quality (Safari et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…The heavy metals such as cadmium (Cd), lead (Pb), chromium (Cr), copper (Cu), and zinc (Zn) are an important group of trace elements, which in concentrations above the norm can negatively influence the development of people, animals (Cd and Pb), and plants (Zn and Cr) (Castaldi et al 2009 ; Safari et al 2015 ). Bioaccumulation of microelements in plants causes their inclusion in the food chain: soil-plant-animal-human.…”
Section: Introductionmentioning
confidence: 99%